A novel tungstate Li3Nd3W2O12 with garnet structure for low-temperature cofired ceramic technology. Issue 4 (April 2020) - Tang, Ying; Yu, Mingyang; Zhang, Zhiwei; Chen, Junqi; Xiang, Huaicheng; Xing, Xianran; Fang, Liang
Abstract: Microwave dielectrics sintered at low temperature are pursued for energy saving and cofiring with cost-effective metallic electrodes (e.g. Cu, Ag and Al). In this study, a novel tungstate low-firing microwave dielectric ceramic, Li3Nd3W2O12, which can realise co-firing with Ag electrode at 940 °C, was synthesised by the conventional solid-state reaction method. According to the X-ray diffraction and Rietveld refinement results, Li3Nd3W2O12 crystallised in the garnet structure with a space group of Ia 3 ¯ d and W 6+ cations fully occupying the octahedral-coordinated site. The optimum microwave dielectric properties with permittivity of ∼9.8, quality factor of ∼36, 800 GHz and temperature coefficient of resonant frequency of ∼ –30 ppm/°C were obtained after sintered at 940 °C. A near-zero temperature coefficient of resonant frequency of +3.6 ppm/°C was achieved in 0.96Li3Nd3W2O12-0.04CaTiO3 ceramics. These properties make tungstate Li3Nd3W2O12 a promising candidate for low-temperature co-fired ceramic technology.